Pesticides as water pollutants and level of risks to environment and people: an example from Central Rift Valley of Ethiopia - Teklu, B. M.; Haileslassie, Amare; Mekuria, Wolde (Springer, 2022)
Sustainable agriculture focuses using agricultural resources with minimum possible negative environmental externality to produce more food. The present study reports the environmental and health risks associated with the use, management and handling of agrochemical in the Central Rift Valley, Ethiopia. Six Woredas (or districts) covering both upstream and downstream areas and major ecosystems were selected. Data were collected using focus group discussion, key informant interviews, field observation and literature review. Pesticide Risks in the Tropics for Man, Environment and Trade tool was used to analyse data. Results indicated that local community’s awareness on use, handling and management of pesticides was low. Applications of insecticides, fungicides and herbicides polluted surface water systems and affected aquatic animals and plants with different level of risk (i.e. from no or insignificant risk to acute and chronic levels). The level of risks of using agrochemical on aquatic animals, human and the environment increased when the agricultural practices changed from good to non-good practices (i.e. increasing frequency of application). The types of agrochemicals determined the levels of risks on aquatic animals, human and the environment. For example, copper hydroxide and Lambda pose high risk, whereas Chlorpyrifos poses possible risk on fish under good agricultural practices. Also, the results indicated that the level of risks of using agrochemicals on fish and aquatic vertebrates was high for few pesticides (e.g. Chlorpyrifos) under both good and bad agricultural practices. The results of the present study support decision makers, practitioners and farmers to put corrective measures when importing agrochemicals, provide targeted risk management schemes including training on safety measures and screen agrochemicals on the market, respectively.